2010
DOI: 10.1167/iovs.09-4613
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Enhancement of α2 Adrenergic Modulation of NMDA Receptor via a Mechanism Independent of Ca2+Channel Blocking

Abstract: These in vitro and in vivo findings demonstrate a novel neural mechanism involving nimodipine enhancement of alpha2 signaling in RGCs. This nimodipine effect appears to be independent of its classic L-type Ca(2+) channel-blocking action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, in the retina the L-type Ca ++ channel plays a dominant role in transmitter release, particularly at photoreceptor and bipolar cell synaptic terminals where glutamate is released (Morgans et al, 2005;Pan, 2000Pan, , 2001Tachibana et al, 1993). Using several commonly used L-type Ca ++ channel blockers, we demonstrated that the depolarization (using a high K+ Ringer) induced Ca ++ signals at IPL were mediated predominantly by the L-type Ca ++ channel (Dong et al, 2010; see also Fig. 12B & 12C).…”
Section: Modulation Of Retinal L-type Ca ++ Channel Function By Brimomentioning
confidence: 71%
See 1 more Smart Citation
“…However, in the retina the L-type Ca ++ channel plays a dominant role in transmitter release, particularly at photoreceptor and bipolar cell synaptic terminals where glutamate is released (Morgans et al, 2005;Pan, 2000Pan, , 2001Tachibana et al, 1993). Using several commonly used L-type Ca ++ channel blockers, we demonstrated that the depolarization (using a high K+ Ringer) induced Ca ++ signals at IPL were mediated predominantly by the L-type Ca ++ channel (Dong et al, 2010; see also Fig. 12B & 12C).…”
Section: Modulation Of Retinal L-type Ca ++ Channel Function By Brimomentioning
confidence: 71%
“…In the rabbit retinal ganglion cell layer, approximately two-thirds of the neurons are RGCs and the remaining one-third are displaced amacrine cells, predominantly displaced starburst amacrine cells (dsACs, 85% of all displace amacrine cells, Vaney, 1984;Vaney et al, 1981). These dsACs can be selectively labeled with a very low dose of DAPI (4',6-diamidino-2-phenylindole, a fluorescent nuclear dye, Vaney et al, 1981;Dong et al, 2010). We found that these dsACs are resistant to NMDA excitotoxicity: the same intravitreal dose of NMDA (3.6 μmol) that produced a substantial cell loss at ganglion cell layer had no effect on dsACs (Fig.…”
Section: Rabbit Retinal Nmda Modelmentioning
confidence: 99%
“…Presence of adrenergic receptors on membranes [11,12] is shown. Highly selective agonist α2adrenoreceptor brimonidine with local administration is in the vitreous body and aqueous fluid of the human eye [13].…”
Section: Membranementioning
confidence: 99%
“…The calcium channels are mainly divided into voltage‐operated calcium ion (Ca 2+ ) channels (VOCCs), inositol 1,4,5‐trisphosphate receptors (IP3Rs) and ryanodine receptors (RyRs) . Clinically, most calcium channel blockers act by antagonising L‐VOCCs (L‐type), and there are three main types of blockers: dihydropyridines, phenylalkylamine and benzothiazepines . However, the existing CCBs inevitably induce some adverse reactions, such as frequent micturition, bradycardia, headaches and lung cancer, and exceed the access and/or affordability of the majority of the world's population who are looking for alternative treatments …”
Section: Introductionmentioning
confidence: 99%